Preparação de catalisadores à base de ferrita de cobalto para aplicação na remoção de contaminantes em efluentes líquidos por processos oxidativos avançados - Oliveira, Jivago Schumacher de (2018)
This work aims to prepare cobalt ferrite (CoFe2O4) based-catalysts for use in the heterogeneous reactions of ozonation, photo-Fenton and photocatalysis aiming the decomposition of recalcitrant organic pollutants from aqueous solutions. Firstly, the CoFe2O4 catalyst was used in the ozonation reaction to decolorize the melanoidin from aqueous solution. Then, CoFe2O4 was incorporated on two inert supports (MgAl2O4 and ZSM-5) in order to evaluate their activities in the degradation of amaranth dye in photo-Fenton reactions under visible and solar irradiation. Finally, the CoFe2O4/Zn2SnO4 photocatalyst was prepared for use in the degradation of rhodamine B under UV irradiation. The materials were characterized by X-ray diffraction, N2 adsorption/desorption isotherms, scanning electron microscopy, X-ray dispersive energy spectroscopy, flame atomic absorption spectrometry, particle-size distribution and infrared spectroscopy. All the materials prepared in this work presented intrinsic properties that culminated in the relevant results for the effective degradation of organic pollutants. The catalytic ozonation of melanoidin in the presence of CoFe2O4 shows remarkable decolorization efficiency (98%) when compared with the non-catalytic ozonation (75%). The MgAl2O4 and ZSM-5-suported CoFe2O4 showed higher activity in the degradation of amaranth dye when compared to the ferrite alone. The CoFe2O4/Zn2SnO4 photocatalyst exhibited a reaction rate about 2.5 times faster than the Zn2SnO4 photocatalyst for the degradation of rhodamine B.